THE IMPORTANCE OF CORPORATE GOVERNANCE IN INCREASING THE INVESTMENT ATTRACTIVENESS OF COMMERCIAL BANKS (International Congress on Economics, Management and Business Studies, 2026)
This scientific thesis examines the role and importance of corporate governance in increasing the investment attractiveness of commercial banks. The investment attractiveness of banks depends on their financial stability, capital adequacy, asset quality, profitability, transparency, and the efficiency of their management system. In particular, corporate governance is considered an important mechanism that ensures a balance of interests among shareholders, management, customers, and investors. The thesis analyzes the impact of the supervisory board, internal control, risk management, information transparency, and independent audit on the investment attractiveness of banks. It also provides recommendations for improving corporate governance in commercial banks of Uzbekistan.
Keywords: Commercial banks, investment attractiveness, corporate governance, supervisory board, bank capital, financial stability, risk management, internal control, transparency, investor confidence.